Clinico-imaging patterns of arterial and venous pathologies in lower limb in R. D. Gardi Medical College Ujjain, Madhya Pradesh - Virmani, Bhavya; Patel, Pratik; Rakholia, Dishant (International Surgery Journal, 2023)
Background: Various arterial and venous pathologies like peripheral arterial disease (PAD), Varicose Veins (VV) and Deep Vein Thrombosis (DVT) are most commonly occurring condition with complain of pain, claudication, swelling, gangrene and dilated veins. Due to late presentation, it is associated with increasing incidence of surgical management which can also lead to amputation of limb in later stages. Aiming at increasing in prevention and conservative management will only be possible on early diagnosis and primordial prevention which requires to find relationship between lifestyle and chronic condition with various vascular disease. Methods: A total of 67 cases were studied over a period of 1.5 years. Their clinical diagnosis along with various radiological diagnosis was compared and its sensitivity, specificity, PPV, NPV, FPR, NPR and accuracy was calculated accordingly. Results: In this study, we found out that vascular disease is associated with sedentary lifestyle, smoking or chewing tobacco or dyslipidaemia. The common presenting symptoms were pain, claudication, swelling, gangrene and dilated veins. In the radiological investigation on comparison between catheter angiography/venography with other modalities showing specificity and sensitivity. Conclusions: In this study, we concluded that colour doppler, CT angiography and catheter angiography has highest accuracy in diagnosing arterial pathology, and Colour Doppler and CT venography has highest accuracy in diagnosing venous pathology.